DAMPAK ASEAN TRADE FACILITATION TERHADAP DAYA SAING DAERAH - Hakim, Dedi Budiman (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2009)
Reducing import tariff rates under the ASEAN-CEPT scheme was considered not significantly to enhance trade flows within the region. Trade facilitation instruments such as mutual recognition arrangement, harmonization on customs procedure and the improvement of other trade-supporting infrastructure were then introduced by the members. Gravity model used in this paper identified a positive impact of such policies in improving trade atmosphere. Local governments can actively play an important role in supporting the conducive environment by providing an efficient bureaucratic system and facilities surrounding harbors. This then reduce transaction cost facing by the private sector and expectedly improve local economic activity in the region.Keyword: ASEAN, Trade Facilitation, Local Government